De barrio a ciudad : El proceso de urbanización neoliberal y post-neoliberal desigual El Alto-La Paz (Bolivia) : 1985-2012 - Díaz, Mariela Paula (2014)
Fil: Díaz, Mariela Paula. FSOC-UBA-CONICET-IMHICIHU.